1999
DOI: 10.1176/ps.50.8.1043
|View full text |Cite
|
Sign up to set email alerts
|

The Goals and Limitations of Israel's Psychiatric Case Register

Abstract: The Israeli Ministry of Health maintains a psychiatric case register that includes basic demographic and clinical information for all psychiatric hospital admissions since 1950. Currently, the case register includes information about some 130,000 people who have been hospitalized. The case register is an important tool in many aspects of mental health care planning, such as delineating problem populations, developing interventions, assessing the ramifications of policies, enacting programs for quality control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…It includes demographic information from birth certificates augmented with data from obstetric and pediatric departments, municipal well-baby clinics, follow-up of vital status, and interviews with some mothers. Its methods have been summarized elsewhere (Harlap et al, 1977;Lichtenberg et al, 1999) and some 80 reports from the study have focused on short-and long-term outcomes. The cohort data were crossed-linked with Israel's national registry of psychiatric disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes demographic information from birth certificates augmented with data from obstetric and pediatric departments, municipal well-baby clinics, follow-up of vital status, and interviews with some mothers. Its methods have been summarized elsewhere (Harlap et al, 1977;Lichtenberg et al, 1999) and some 80 reports from the study have focused on short-and long-term outcomes. The cohort data were crossed-linked with Israel's national registry of psychiatric disease.…”
Section: Methodsmentioning
confidence: 99%
“…Established in the Ministry of Health in 1950, the Psychiatric Registry receives information about all psychiatric diagnoses, including reports from patients admitted to psychiatric hospitals, psychiatric wards within general hospitals, and psychiatric day-care facilities. The registry's design and methods have been described in detail elsewhere and it has been used for clinical and epidemiologic research in schizophrenia (Harlap et al, 1977;Lichtenberg et al, 1999). In the past decade, studies using the Jerusalem Perinatal Study, linked to other databases in Israel, showed that the offspring' identification numbers, sex, birth dates, and basic demographic information, including parental ages, were more than 99.9% accurate (Lichtenberg et al, 1999;Laor et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Run by the Ministry of Health since 1950, 13 the Registry contains a record of all admissions to psychiatric wards and day facilities and includes dates of admission and discharge and a single discharge diagnosis for each episode, assigned by a board-certified psychiatrist. These diagnoses are coded with the ICD; codes from earlier years have been updated to 10th Revision (ICD-10), and those for psychotic disorders have been validated recently.…”
Section: Subjectsmentioning
confidence: 99%
“…The PCR is legally mandated to maintain a cumulative record of all psychiatric hospitalizations [12][13] . The PCR provided the subjects' diagnoses upon admission and discharge as well as socio-demographic information.…”
Section: Identification Of Persons Diagnosed With Schizophreniamentioning
confidence: 99%